Konflik Keluarga Terhadap Motivasi Belajar Mahasiswa Program Studi Keperawatan Program Sarjana di Universitas Harapan Bangsa : Family Conflict on The Learning Motivation of Students in The Nursing Student Program at The University of Harapan Bangsa - Giriandra Tegar Rachman; Adiratna Sekar Siwi, Adiratna Sekar Siwi; Indri Heri Susanti (Politeknik Insan Husada Surakarta, 2024)
Students are individuals who are studying at the university level, both public and private or other institutions at the same level as universities. One of the factors that influence student achievement is motivation. Motivation makes students learn harder, be resilient, persevere and have full concentration in the learning process. The state of the influence of family support is closely related to the success of student achievement or learning motivation. This study aims to determine whether there is an influence of family conflict on student learning motivation, this type of research is quantitative research using correlational research methods with a cross sectional approach. The instruments used were the FHS-24 (Family Harmony Scale) questionnaire and the learning motivation questionnaire. This research was conducted for two months. Sampling with the criteria of age, gender, and marital status of parents, using non probability sampling with random sampling. The sample of this study totalled 207 students. The statistical test used is spearman rank. The results showed that most of the respondents were 20 years old (27.1%), female, 171 students (82.6%), and with married parents’ marital status as many as 182 students (87.9%). The results of the spearman rank test showed a p value of 0.004 <0.05 with a correlation value of -0.201, which means that the higher the family conflict, the higher the family conflict.